2018
DOI: 10.1200/jco.2018.36.6_suppl.665
|View full text |Cite
|
Sign up to set email alerts
|

A cost-benefit analysis for sonographic screening for renal tumors.

Abstract: 665 Background: In the last 2 decades, the rates of metastatic Renal Cell Carcinoma (RCC) at diagnosis declined from 33% to 17%This fact is attributed to massive penetration of cross sectional imaging leading to a marked stage migration. The cost of targeted therapy for metastatic RCC patients is very high. These trends led us to hypothesize that screening for RCC with ultrasound may be cost effective. Objective: To assess the cost effectiveness of screening with ultrasound for renal tumors in the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, two recent studies have shown otherwise. Using the Markov model, Roizman et al proposed that screening for RCC in the general population using ultrasonography could be a cost-effective option 23. Another study used a similar model and suggested that RCC screening in the general population may be cost-effective in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two recent studies have shown otherwise. Using the Markov model, Roizman et al proposed that screening for RCC in the general population using ultrasonography could be a cost-effective option 23. Another study used a similar model and suggested that RCC screening in the general population may be cost-effective in males.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Markov model, Roizman et al proposed that screening for RCC in the general population using ultrasonography could be a cost-effective option. 23 Another study used a similar model and suggested that RCC screening in the general population may be cost-effective in males. This costeffectiveness was not demonstrated in females due to a lower prevalence of RCC.…”
Section: Discussionmentioning
confidence: 99%